WORLDLY AND UNWORLDLY FEELINGS, FABRICATION AND LETTING GO. Issue 2 (3rd July 2018) - Roth, Jonathan M.
ABSTRACT: This paper proposes a framework for understanding vedanā and emotion in relation to each other, and both of them in relation to awakening. The vedanā (or feeling tone) that arises in mental experience will be shown to be central to emotion. Western views of emotion will be examined alongside some of the Buddha's teachings on vedanā . The paper will show mental vedanā, and human emotion in the context of the two psychological orientations of 'fabrication' and 'letting go', which are then correlated with the Buddha's notions of 'worldly' and 'unworldly' feelings. The paper proposes that such contextualisation is useful towards the development of a clear intellectual understanding of the nature of feelings, while (more importantly) it could support practitioners in a process of meditative inquiry and transformation.